Perception of healthcare professionals in university college hospital, ibadan toward wound care (2016)
Background: A survey of perception of healthcare workers in a tertiary hospital [University College Hospital (UCH), Ibadan] was done with a view to determine the need to introduce a curriculum in wound care for healthcare workers. Materials and Methods: A self-administered questionnaire was used to capture data related to knowledge and practices on wound care from healthcare workers in UCH, Ibadan. Descriptive analysis was done using the Statistical Package for the Social Sciences version 21 software (SPSS Inc., Chicago, IL, USA). Results: One hundred and four healthcare professionals working in UCH, Ibadan, comprising doctors, nurses, and physiotherapist, with 61.1% over 10 years of experience in wound care were surveyed. Seventy- seven percent agree or strongly agree that healthcare professionals are knowledgeable about best practices in wound care. 50.5% agree or strongly agree that UCH operates best practices in wound care while 49% agree or strongly agree that wound assessment is standardized in the hospital. 96.2% agree or strongly agree that an interprofessional wound care course will be beneficial to healthcare professionals and that it will enable healthcare professionals speak the same language with regard to wounds. Conclusion: Teamwork and definite wound care policy/protocol are essential for excellent outcomes in wound care. Introduction of this approach will enhance knowledge translation and encourage best practice in our health institutions.